Customer Switcising Behavior In Retail Banking Services: A Case Study In Klang Valley - Hanim Hj Misbah; Nor Haziah Hashim (Universiti Sains Islam Malaysia, 2024)
This research aims to explore the determinants of customer switching behavior and switching barriers in retail banking services. Therefore, the research was divided into two study, Study I: Switching Determinants and Study II: Switching Barriers. The study used self-administered survey for data collection method. Both self-administered survey were designed to collect data on three parts; Part A to measure customers' knowledge and understanding towards Islamic Banking system, Part B on switching determinants / switching baniers and Part C on respondents profile. The findings in Part A for Study I and 11 stated that customers are aware and understand about the Islamic banking system and services. Meanwhile, findings in Part B for Study I suggested seven factors influencing customers' decision to switch. The factors were namely employee and service failure, pricing, attraction, inconvenience, waiting, location and involuntary. On the other hand, findings for Part B, Study I1 generated an eight-factor solution. These factors provide insights on factors influencing customers' decision to stay with their current bank. Among the factors were service recovery, location, pricing, switching inconveniences, convenience to stay, switching cost and confidence, relationship investment and lastly, apathy. To summarize, it is hoped that these fmdings will provide guidelines and suggestion to the banker on how to attract new customer, avoid existing customers from switching and improve customer loyalty thereby remain competitive.